Jane Tolmach Campaign Statement - Jane Tolmach::::::
This campaign statement criticizes Chuck Imbrecht for relying heavily on out-of-county corporate and special interest funding, arguing that more than 75% of his campaign contributions since June have come from outside Ventura County. It contrasts his claim of being a local "reform candidate" with his prior Nixon administration appointments and financial backing from corporations and lobbyists. The statement specifically questions large contributions from "United for California," describing it as a vehicle for anonymous special-interest funding. The document calls on Imbrecht to publicly disclose his contributors and any commitments made in exchange for their financial support, framing the election as a choice between local control and outside influence.